Winter Buckwheat Grain: The Dynamic Pattern of the Mechanical Properties of the Main Fraction - Mar'in V.; Vereshchagin A.; Bychin N. (Техника и технология пищевых производств)
As quality requirements get lower and lower, the quality of buckwheat grain meant for buckwheat groats is deteriorating. The most typical example is winter buckwheat grain. Buckwheat grain has to be sorted according to various fractions before scouring. Thus, the mechanical properties of these fractions remain a relevant field of study. The research features the dynamic pattern in the mechanical properties of the main fractions of winter buckwheat grain according to fraction before and after storage. The research subject is fractions of buckwheat sorted according to grain size before scouring. The buckwheat grain was harvested in the foothills of the Altai Territory in May 2015; it meets the necessary standards. There were twelve samples: six samples were harvested and sent for recycling (May 2015); other six samples were stored for eight months up to March 2016. The buckwheat did not pass the temperature treatment stage. The smaller fractions revealed a greater deformation before and after storage. That can lead to a higher deformation rate during scouring. Thus, the changes in the mechanical properties of winter buckwheat grain occur differently for each fraction.